Metode Penelitian Korelasi Pada Manajemen Pendidikan Islam - Ai Ina Afifah Munawwaroh (Gunung Djati Conference Series, 2023)
The purpose of this research is to identify challenges, develop strategies, and improve effective management practices in the context of Islamic education; (2) This paper will further describe the analysis of research methodology to obtain knowledge that can answer various questions or can solve a problem that exists in solving problems and to obtain scientific knowledge; (3) The results of correlation research can be in the form of positive correlations, negative correlations, weak or insignificant correlations, or nonlinear correlations; (4) The conclusion from this text is that research in Islamic education management aims to understand and improve management aspects related to Islamic education. Several topics that can become the focus of research in Islamic education management include school leadership and management, curriculum management, management of educational quality, financial and resource management, and management of stakeholder relationships.